Preobrati v organizirani večstanovanjski gradnji - koncepti, tehnologija, financiranje - Fikfak, Alenka (Urbani izziv, 2002)
Organised multi-unit housing, which appeared soon after the industrial revolution, reaching full swing in the 20. century, encompasses a large part of the housing stock. Its first consequence was the unlimited expansion of cities and new settlements into the countryside. In this sense the flow of people and the need for new residential areas had a massive impact on urban environments, the culture of living and living quality. These are all still valid criteria for setting guidelines for new housing estates. The planning approaches changed continuously aligned to the introduction of new concepts, technological possibilities and even financing methods. These are all startingpoints for evaluating the distance between Slovenian practice and external events and establishment of new physical forms, whereby we used comparisons between important European and foreign examples, which represent breakthroughs in urban layouts and architectural design.
Keywords: financiranje; mesta; stanovanja; stanovanjska gradnja; stanovanjska politika; urbanism; urbanizem; večstanovanjske zgradbe